The Relationship between Emotional Intelligence and Academic Achievement among Undergraduate Students in Kazakhstan. The Case of Two Universities - Fillipova, Lyudmila (Nazarbayev University Graduate School of Education, 2019)
Academic achievement and performance of students in higher education settings is an integral part of learning process, however nowadays, the soft skills of future specialists are not of small importance as well. Although, the Emotional Intelligence had been recognized as an independent notion in the second part of twentieth century, still most experts in the spheres of psychology, education and management find this area rather ambiguous. There were several studies which had been focused on the relationship between emotional intelligence and academic achievement before. However, few research studies in this sphere had been conducted in Kazakhstan. Thus, there is a need for higher education institutions to identify the significance of EI elements for students’ success during the learning process. The study focuses on the link between emotional intelligence and academic achievement among the Autonomous University and the Regional University undergraduate students. The results of the study would contribute to higher education system in Kazakhstan, as administrators, managers and faculty members may be provided with the current emotional intelligence level of undergraduate students from two institutions. Furthermore, other higher education institutions may use the findings of the current research study in order to facilitate students’ emotional intelligence level inserting related activities in their curricula. This study employs a cross-sectional correlational design (Field, 2009; Mujis 2004; Szafran, 2011). The purpose of the study was to identify the relationship between emotional intelligence and academic achievement among undergraduate students. To define the level of emotional intelligence, the ESAP (Emotional Skills Assessment Process) questionnaire was employed to collect data, so that the research study was focused on four main competencies: interpersonal, leadership, self-management and intrapersonal. To obtain the information about students’ academic achievement, selfreported percentage had been used. The data had been collected in two Kazakhstani universities. The sample consisted of 239 undergraduate students, 141 and 98 undergraduate from two universities (Regional and Autonomous) respectively. The sample was recruited on non-probability basis, due to voluntary participation in the research study. During the research study descriptive, inferential and correlational statistical analyses had been employed. The Statistical Package for the Social Sciences (SPSS) had been used to make the statistical analyses of the collected data. The study presents the information on the general emotional intelligence level of undergraduate students of two universities. Similarly, the research study demonstrates the three levels of academic achievement of students: high-, average- and lower-achieving and their correlation with emotional intelligence competencies. Furthermore, the study explores students’ emotional intelligence level differentiated by their age and gender.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Emotional Intelligence; education system; higher education settings; HIS; cross-sectional correlational design